2021
DOI: 10.3389/fnins.2021.636348
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin1-ErbB4 Signaling in Spinal Cord Participates in Electroacupuncture Analgesia in Inflammatory Pain

Abstract: Chronic inflammatory pain is a severe clinical symptom that aggravates the life quality of patients and places a huge economic burden on individuals and society. As one complementary and alternative therapy, electroacupuncture (EA) is widely used in clinical practice to treat chronic inflammatory pain based on its safety and efficacy. Previous studies have revealed the potential role of adenosine, neuropeptides, and inflammatory factors in EA analgesia in various pain models, but the identity of some of the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 56 publications
1
7
0
1
Order By: Relevance
“…Electroacupuncture is an effective and safe alternative therapy for treating anxiety disorders ( Errington-Evans, 2012 ). Studies have shown that EA at the Zusanli and Sanyinjiao acupoints can reduce the mechanical and thermal pain sensitivities of inflammatory pain induced by CFA in mice models ( Wan et al, 2021 ). Acupuncture of the Zusanli acupoint can improve motor function and anxiety-like behavior in Parkinson’s disease mice models ( Jang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Electroacupuncture is an effective and safe alternative therapy for treating anxiety disorders ( Errington-Evans, 2012 ). Studies have shown that EA at the Zusanli and Sanyinjiao acupoints can reduce the mechanical and thermal pain sensitivities of inflammatory pain induced by CFA in mice models ( Wan et al, 2021 ). Acupuncture of the Zusanli acupoint can improve motor function and anxiety-like behavior in Parkinson’s disease mice models ( Jang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…ERBB4 encodes a receptor tyrosine kinase and promotes inhibitory synapse formation in pyramidal neurons 49 . ERBB4 mediates amyloid β-induced neurotoxicity, which is a biomarker for Alzheimer’s disease 50 , and Neuregulin1-ERBB4 signaling regulates the inflammatory pain of electroacupuncture analgesia in the spinal cord 51 . Moreover, the function of ERBB4 in dopamine neurons is related to depression-like behaviors, and it regulates the homeostasis of extracellular dopamine and norepinephrine in catecholaminergic cells 52 .…”
Section: Discussionmentioning
confidence: 99%
“…141 Some studies showed that EA can increase NRG1 expressions in muscles, proving that there is a potential relationship between EA and NRG1. 142,143 Wan et al 98 found that EA alleviated pain hypersensitivity because it increased NRG1 expressions in SC of CFA-induced inflammatory pain mice models. This analgesic effect was partly mediated by NRG1-ErbB4 signaling.…”
Section: Gabaergic Interneuronmentioning
confidence: 99%